Humor in the classroom a guide for language teachers and educational researchers - Bell, Nancy 1969-; Pomerantz, Anne (Routledge, 2016)
Humor in the Classroom provides practical, research-based answers to questions that educational researchers and language teachers might have about the social and cognitive benefits that humor and language play afford in classroom discourse and additional language learning. The book considers the ways in which humor, language play, and creativity can construct new possibilities for classroom identity, critique prevailing norms, and reconfigure particular relations of power.